Healthy Ageing: A Basic Concept - Chalise, Hom Nath (Asian Journal of Population Sciences, 2023)
Rapid population aging is a characteristic of the 21st century, regardless of a nation’s level of development. An aging global population results in a burden in medical and social demographic problems worldwide. Addressing this problem is the highest priority for the care of the aging population worldwide. Healthy aging is an individual lived experience that is influenced by healthy behaviours over the course of a lifetime. This includes a person’s ability to: meet their basic needs; learn, grow and make decisions; be mobile; build and maintain relationships, and contribute to society. For the promotion of healthy aging, a healthy lifestyle is important. A healthy lifestyle for older adults includes healthy eating, regular physical activity, staying at a healthy weight, improving mental health, social participation, regular health check-ups and health screening, no smoking, and taking steps to prevent falls.